"Фабрика слез": [роман] / Вера и Марина Воробей - Воробей Вера (Первый роман, 2006)
Экземпляры: ф. 13 (20140227) / Инвентарный номер: 38846 / Цена: 20.00 / Авт.знак: В 75 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6